(untitled) (Portuguese Journal of Family Medicine and General Practice, 2002)
Economic evaluation of medicines is a new area of knowledge which aims to help physicians and decision makers to choose among therapeutic alternatives based on the relation between the cost of medicines and the benefits arising from their use. The main types of economic evaluation of medicines are: minimisation of costs, cost-benefit, cost-effectiveness, and cost-usefulness. General practitioners, being prescribers and generators of costs for the National Health Service, should have some notions on economic evaluation of medicines which will allow them to critically read the pharmacoeconomics articles that are made more and more available to them.